DEVELOPING RELIGIOUS BASED HOTS ASSESMENT BOOK IN SCIENCE SUBJECT TO INCREASE TEACHERS’ COMPETENCE IN DESIGNING HOTS ASSESSMENT AT ELEMENTARY SCHOOL - Dwi Indah Mulyani; Sri Utaminingsih, Slamet Utomo (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to determine: 1) the development of a religious-based HOTS assessment book; 2) the effectiveness of the book to improve teachers’ competence in preparing religious-based HOTS assessments for grade 4 elementary school in science subject content. This research was a development research (RnD) adapted from Borg and Gall development model with the following procedures: 1) Identification of Potentials and Problems; 2) Data Collection; 3) Product Design; 4) Design Validation; 5) Product Revision I; 6) Product Trial; 7) Product Revision II; 8) Trial Use; 9) Revision of the End Product; and 10) Product Dissemination. The product of this research was a religious-based HOTS assessment book in science subject content for grade IV SD. The feasibility of the book was shown through validation (material and media testing) by two material and media experts, getting an average validation score of 80.49 with a very good category. The effectiveness of using the book was proven by the t-test which obtained t count = -9.892 < t table = 1.72 so that Ha was accepted. The conclusion of this study was that the religious-based HOTS assessment book increased teachers’ competence in compiling HOTS assessments at elementary schools. Suggestions in this study included that teachers should use this HOTS-based assessment book to improve their competence in HOTS assessments.